ADDITION OF THE TRUST FACTOR IN THE ASSESSMENT OF CRIMINOGENIC NEEDS AS THE BASIS OF THE WBP PERSONALITY DEVELOPMENT AND GUIDANCE PROGRAM - Muhammad Ridha Intifadha; Hafizh Nuur Afif Elhadi Mamesah; Hannie Riestyaninda (Polteknik Ilmu Pemasyarakatan, 2022)
This research discusses guidance and mentoring programs that have been running in the Correctional Centre/State Detention Centre/Correctional Centre for Children/Parole Office, especially in religious awareness programs that do not have a solid basis. This is because the factor of belief or religiosity is not included in the factor of criminogenic needs which forms the basis of program development. This study further examines the seven factors in criminogenic needs assessment through social bond theory, as well as the relationship between crime and one's adherence to one's religion. The data used in this study were obtained through a criminogenic needs assessment of 770 inmates in DKI Jakarta and mentoring program activities that have been running at South Jakarta and Metro Parole Office. The results of this study found that personality development and mentoring programs in the form of religious awareness activities that have been running do not have a solid basis based on the criminogenic needs of inmates. Therefore, the authors hope that this research can be used as a consideration in adding the belief factor in the assessment of criminogenic needs as the basis for the inmates personality development and mentoring program.